Uptake of Treatment as Prevention for HIV and Continuum of Care Among HIV-Positive Men Who Have Sex With Men in Nigeria. (1st March 2015) - Charurat, Man E.; Emmanuel, Benjamin; Akolo, Christopher; Keshinro, Babajide; Nowak, Rebecca G.; Kennedy, Sara; Orazulike, Ifeanyi; Ake, Julie; Njoku, Ogbonnaya; Baral, Stefan; Blattner, William
Abstract : Background: Experimental evidence has shown that treatment of HIV infection with antiretroviral therapy (ART) prevents heterosexual transmission of HIV to an uninfected partner. However, the "real-world" application of this strategy to key populations such as men who have sex with men (MSM) has been limited. We report findings on acceptability of a treatment as prevention (TasP) strategy among HIV-infected MSM at a Trusted Community Center providing comprehensive HIV prevention and treatment services to MSM in Abuja, Nigeria. Methods: Using respondent-driven sampling (RDS), MSM who were 16 years and older and have engaged in either receptive or insertive anal intercourse within the previous 12 months were recruited into a prospective combination HIV prevention and treatment study (TRUST). Two weeks after enrollment, HIV testing and counseling was conducted. At each 3-month follow-up visits, HIV-infected individuals underwent clinical and laboratory evaluation, including CD4 count, plasma HIV viral load, immediate 3 weekly sessions of ART preparation, and then ART initiation per TasP strategy irrespective of CD4 count. Reasons for not engaging in pre-TasP preparation and TasP were documented. Characteristics associated with TasP engagement and loss to follow-up (LTFU) were determined using logistic and Cox regression, respectively. Results: Of 186 HIV-positive MSM enrolled, 58 (31.2%) were on ART at the time of recruitment, whereas 128 (68.8%) were ART-naive and provided opportunity for engaging TasP. Of these, 70 (54.7%) engaged in TasP. Compared with MSM who did not engage in TasP, those who engaged had significantly lower mean CD4 count ( P = 0.001), were more likely to be Christian ( P = 0.01), and had disclosed being MSM to family ( P = 0.02) or health care providers ( P = 0.02). In multivariate models, disclosure of being MSM to health care providers remained significantly associated with uptake of TasP. Among individuals engaged in TasP, 10% were LTFU in care at 18 months since enrollment. Being engaged in TasP (relative hazards = 0.08, P < 0.001) and on ART (relative hazards = 0.17, P < 0.001) were associated with decreased risk of LTFU. Conclusions: Although there was high acceptance of HIV testing and low LTFU among individuals who were already on ART or engaged in TasP, a higher than expected proportion did not engage in TasP, suggesting the need for customized treatment preparation and an increase in enabling environments to support HIV treatment access with this key population.